SUSTAINABLE WASTE MANAGEMENT: A CASE FROM INDIAN CEMENT INDUSTRY - pathak, Priyanka; Gupta, Sumit; Dangayach, Govind Sharan (Brazilian Journal of Operations & Production Management, 2015)
Sustainability means meeting the needs of the present without compromising the ability of future generations to meet their own needs, and Sustainable Waste Management is using waste produced efficiently so that use of amount of material resources get reduced. India, is the second amongst cement producers in the world with a total capacity of 245.40 Million Tonnes (MT), has a huge cement industry and produces about 7% of world’s total production. The Indian cement industry has on one hand, enormous pressure to increase profit and margins, while on other; there is considerable public interest on a sustainable and environment friendly usage of natural resources. The objective of this paper is to pursue sustainable waste management for a cement industry through replacement of coal with some alternative fuel, which actually belongs to the group of hazardous wastes and which could benefit the plant economically and environmentally, and improve sustainability of plant. The use of alternative fuels will help in reducing energy costs and providing a competitive edge for a cement plant. Furthermore, this will reduce the burden of waste disposal considerably. So, it also supports to fulfilling Sustainable Waste Management issues